Perlindungan Hukum Pemegang Saham Minoritas PT (Persero) dalam Pembentukan Anak Perusahaan BUMN - Hamanda Tiara Emanuella (MLJ Merdeka Law Journal, 2021)
BUMN (Persero) is regulated in UU 19 of 2003 on BUMN. BUMN hold 50% or more of share as a major controlled, the minority share can be owned by other parties with IPO mechanism. BUMN is including the subject of Law Number 40 of 2007 on Limited Liability Company, which specifically regulates the rights of shareholders. However, the problem is related to when the BUMN carrying out its business activities establishes a subsidiary based on the decision of the GMS, where the majority shareholder who is the largest shareholder is on the side of him, which makes the rights of the minority shareholder neglected. The purpose of this study is to analyze the pattern of protection for minority shareholders of Limited Liability Company according to Corporat Law system and the legal remedies of minority shareholders in protecting their rights to action. This research is a normative legal research with descriptive analytical research. The result of this study is that legal protection for minority shareholders of BUMN is regulated in BUMN Law and Limited Liability Company Law but there are the rights of these shareholders which are only fulfilled if they receive support from the majority shareholder, so that the sense of justice of minority shareholders is not protected. , however, there are efforts to settle disputes that can be taken both litigation and non-litigation, especially Acts against the Law (1365 BW) with the mechanism regulated in the Law on Company LawDOI: https://doi.org/10.26905/mlj.v2i2.7166